Primary cutaneous mucinous carcinoma of the penis - Robinson, Michael; Kelly, John; Biberdorf, Darren; McAuley, Iain (Canadian Urological Association Journal, 2014)
Primary cutaneous mucinous carcinoma (PCMC) is a rare, slow growing, malignant neoplasm arising from the sweat glands. Lesions are most commonly seen on the head and neck, and frequently mistaken for metastases from more common primary sites, such as the breast, gastrointestinal tract, lung, ovary, or prostate. We present what we believe is the first reported case of PCMC involving the penis.